STUDY OF IMMUNOSTIMULATORY PROPERTIES OF ADJUVANT MONTANIDE™ GEL 01 AND VARIOUS INACTIVANTS IN THE COMPOSITION OF INACTIVATED CULTURE CAMEL SMALLPOX VACCINE - Maikhin, K. T.; Berdikulov, M. A.; Mussayeva, G. K.; Zhussambayeva, S. I. (ЗКАТУ им. Жангир хана, 2024)
Chemical methods of virus inactivation have found wide application in production due to their ease of use, gentle effect on the antigenic structure of pathogens, reliable inactivation and high reproducibility of results. Of all known chemical compounds used as inactivants, formaldehyde and ß-propiolactone are the most widely used. In experiments to determine the inactivation mode of the camel pox virus, a culture strain that had undergone 15 consecutive passages on the culture of lamb kidney cells was used. For virus inactivation, formaldehyde was used at concentrations of 0.02; 0.03; 0.05 and 0.1% relative to the total biomass volume. During the course of the experiment, the timing of complete inactivation of the virus by OM was determined at temperatures of 4°C, 27°C and 37°C, at pH of the suspension 7.4-7.6. The initial biological activity was 6.25 lgTCD50/cm3. The choice of adjuvant in vaccine development is critical to the properties of the vaccine. There is no universal adjuvant and there is always a trade-off between safety and efficacy. Consequently, the adjuvant chosen will depend on the target species, antigen, route of inoculation and the desired immune response and its duration. This study provides direct evidence that Montanide™ GEL 01 can act as a potent adjuvant in a synthetic peptide-based vaccine and represents an easy-to-use and inexpensive veterinary vaccine with a higher safety profile for large animals.
Maikhin, K. T. Study of immunostimulatory properties of adjuvant montanide™ gel 01 and various inactivants in the composition of inactivated culture camel smallpox vaccine / K. T. Maikhin, M. A. Berdikulov, G. K. Mussayeva, S. I. Zhussambayeva [et al.]. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-1 (75). Ч. І. - Р. 278-286 (Uraksk).
Keywords: camels; smallpox; smallpox vaccine virus; адъювант; attenuation; infection; зкату; научный журнал